Rotating perennial forages into annual wheat cropping systems: Correlations between plant available soil and grain mineral concentrations. Issue 3 (20th June 2022) - Clemensen, Andrea K.; Duke, Sara E.; Franco, José G.; Grusak, Michael A.; Liebig, Mark A.; Hendrickson, John R.; Archer, David W.
Abstract: Correlations between plant available soil and grain mineral concentrations are often assumed, yet few studies examine these associations. Here, soil and wheat grain samples were analyzed from a semi‐arid dryland cropping study in the northern Great Plains conducted between 2006 and 2011. Continuous spring wheat (fertilized) ( Triticum aestivum L; CSW) was compared with wheat following 5 yr of perennial forages of either alfalfa ( Medicago sativa L.), intermediate wheatgrass (fertilized) ( Thinopyrum intermedium (Host) Barkw. & D.R. Dewey sbsp. Intermedium ; IWG), or an alfalfa/intermediate wheatgrass mixture (fertilized; MIX). Wheat performance (yield, 1, 000 kernel weight [TKW], and crude protein [CP] concentration), and associations between 11 plant available soil mineral concentrations and 11 wheat grain mineral concentrations were assessed. Wheat following alfalfa had greater yield than all treatments, greater TKW than CSW, greater CP than IWG and CSW, but lower grain Zn concentration than IWG ( p ≤ .05). Wheat grain following IWG had greater Fe and Mn concentration than MIX, greater Mg concentration than CSW, and lower S concentration than all treatments ( p < .05). Multivariate correlation analysis showed positive correlations between plant available soil and grain B, Mg, Mn, and S concentrations ( p ≤ .02), while plant available soil and grain Zn and Ca concentrations showed negative associations ( p ≤ .05). Rotating perennial forage phases into wheat cropping systems increased wheat yield and CP but reduced certain plant available soil minerals. Although rotating perennials into annual cropping systems can benefit some soil quality parameters it may also diminish plant available soil minerals, influencing fertility recommendations. Core Ideas: Mineral associations between soil and wheat grain were assessed. Soil and grain Zn and Ca concentrations were negatively ( p ≤ .05) correlated. Soil and grain B, Mg, Mn, and S concentrations were positively ( p ≤ .02) correlated. Plant available soil Fe, Mn, P, S, and Zn concentrations were diminished under perennial forages ( p ≤ .05).